Charge Stratification and Fuel/Air Ratio Effect on the Efficiency of (ICADE) I. C. Engine Cycle - Abed Dhahad, Hayder Abed (Al-Khwarizmi Engineering Journal, 2011)
The Isolated Combustion and Diluted Expansion (ICADE) internal combustion engine cycle combines the advantages of constant volume combustion of the Otto cycle with the high compression ratio of the Diesel cycle.   This work studies the effect of isolated air mass (charge stratification) on the efficiency of the cycle; the analysis shows that the decrease of isolated air mass will increase the efficiency of the cycle and the large dilution air mass will quench all NOx forming reactions and reduce unburned hydrocarbons. Furthermore, the effect of Fuel / Air ratio on the efficiency shows that the increase of Fuel / Air ratio will increase efficiency of the cycle.